CLINICAL AND PARACLINICAL CHARACTERISTICS OF STAGE II–IIIA BREAST CANCER PATIENTS AT THANH HOA CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Overview: Breast cancer (BC) is the most common cancer in women and also the leading cause of cancer-related mortality among women. However, there are differences in the clinical and paraclinical characteristics of patients across different geographical regions. We conducted a study on the clinical and paraclinical characteristics of BC patients diagnosed at Thanh Hoa Cancer Hospital to clarify the differences compared to other geographical areas.Patients and Methods: Data were collected from the medical records of 87 patients diagnosed with stage II–IIIA BC at Thanh Hoa Cancer Hospital from February 2020 to December 2024.Results:The mean age at diagnosis was 46.9 ± 7.6 years, primarily in the 40–59 age group (78.1%). The majority of patients detected the disease by self-palpation of a breast mass (72.4%) and presented for examination within 6 months (65.5%) of discovering the mass. The most common tumor location was the left breast (65.5%) and the upper outer quadrant (71.3%). Regarding molecular biology, the rate of positive hormone receptors (ER and/or PR) was 85.1%; HER2 negativity accounted for 62.1%, and Ki67 > 20% accounted for 70.1%. The Luminal B subtype had the highest prevalence (55.2%). Conclusion: Our study population was diagnosed with the disease at a younger age and had a longer time to treatment access compared to previously conducted studies.
Keywords: Breast cancer, early-stage breast cancer, breast cancer epidemiology.